(3CNdGb GdfHi Udi Gddg Ydjg hSde hBOGHgs - (3CHh YHO Gddg Hf MjGf GdCUagGfjs
(3ChdgG (B:s
(3GdMeO ddg Ydi SJQg eG CYLR GdeSJhQ Yf TcQg eG PcQ ef MSf Ndb QShd Gddg Udi Gddg Ydjg hSde hcQeg hYahg hLhOg hSNGFg hTLGYJg s
(3BNQgG (B:s
(3bGd fgi GdfHi Udi Gddg Ydjg hSde Cf jCcd HGdTeGd BNQ GdcJGH hddg GdMeO Cgd GdMeO hhdjg hGdUdGI Ydi eMeO YHOg hfHjg s
(3GdfSNI HgG MhGTs
(3Ydi GdfSNI SeGYGJ ef GdbQf GdSGOSs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdabg GdESdGejs